Establishing patterns of change in the efficiency of regulated intersection operation considering the permitted movement directions - Boikiv, Mykola; Postranskyy, Taras; Afonin, Maksym (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is a regulated intersection of city streets. The main task being solved is the reduction of queue lengths on approaches to such intersections by organizational measures. As a result of the research, patterns of change in queue lengths in front of the stop line were revealed, taking into consideration the specialization of traffic lanes and the distribution of traffic flows by directions. It was established that with an increase in the share of left-turning vehicles in the lane by 15 % and above, there is an increase in the length of the queue before the intersection from 45 to 80 m. The results indicate that when choosing a traffic pattern at the intersection, it is necessary to take into consideration not only the intensity of the flow itself but also the proportion of vehicles performing certain maneuvers (in this work, turning left is considered). A feature of the results is that they are obtained using simulation tools. This research method has made it possible to derive the value of the length of the queue in front of the intersection, changing the load on the approach from 200 to 1000 vehicle/h and the share of left-turning vehicles from 5 to 15 %. In addition, using a simulation model, it was checked how the intersection functions under various traffic management schemes on it when the input parameters of traffic flows change. The research results are recommended to be used in the development of traffic management schemes at regulated intersections. When determining the permitted directions of movement in the lanes, it is necessary to take into consideration the patterns of change in the length of queues before the intersection since under certain circumstances they may exceed critical values.